2023
DOI: 10.3390/axioms12030257
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Anisotropy Pressure in Self-Gravitational Systems in f(G) Gravity

Abstract: This investigation aims to explore certain variables which are considered responsible for generating pressure anisotropy in dynamical spherically symmetric stellar systems against the background of the stringy-inspired Gauss–Bonnet modification of general relativity. We explore the hydrostatic equilibrium of self-gravitating systems by taking into account the modified form of Tolman–Oppenheimer–Volkoff for the quadratic-f(G) gravitational model. In this respect, we formulate a differential equation in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Some interesting and charming work on different modified theories of gravities can be seen in refs. [58][59][60][61][62][63][64][65][66][67] Skripkin's model, proposed in 1960 by Skripkin, [68] was the first known model that satisfied the conditions of zero expansion and non-dissipative arrangement of a compact fluid with constant energy density. This study focused on the evolution of compact fluid following a central explosion and indicated that the center of the fluid distribution should be surrounded by a Minkowskian cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some interesting and charming work on different modified theories of gravities can be seen in refs. [58][59][60][61][62][63][64][65][66][67] Skripkin's model, proposed in 1960 by Skripkin, [68] was the first known model that satisfied the conditions of zero expansion and non-dissipative arrangement of a compact fluid with constant energy density. This study focused on the evolution of compact fluid following a central explosion and indicated that the center of the fluid distribution should be surrounded by a Minkowskian cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Some interesting and charming work on different modified theories of gravities can be seen in refs. [58–67]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researching stellar structures under modified gravity can provide new insights into processes like as gravitational collapse, neutron star mergers, and the behavior of matter in extreme gravitational fields, eventually improving our understanding of the Universe's complexities. Some of these are f (R) [17][18][19][20], f (G) [21][22][23], f (R, T) [24][25][26][27], f (Q) [28,29], f (R, A) [30][31][32], f (R, f) [33][34][35] and f (R, f, X) [36][37][38] modified gravity theories. In these theories, the equations governing gravity are modified to include additional terms that could explain the observed acceleration of the Universe.…”
Section: Introductionmentioning
confidence: 99%
“…Elizalde et al [20] examined the proposed unified theory of exponential modified gravity, which accounts for early-time inflation and late-time acceleration, successfully navigating local tests and cosmological bounds, yet revealing instability during the inflationary era, with late-time evolution resembling that of the ΛCDM model for dark energy. Granda [21] investigated unified inflation and late-time accelerated expansion, integrating exponential and R 2 corrections within modified gravity theory, while Dolgov and Kawasaki [22] demonstrated that recent proposals attributing cosmic acceleration to small curvature modification of gravity encounter severe instabilities and conflict with established gravitational interaction properties. Bahamonde along his collaborators [7] analysed a large number of cosmological models and show how the stability conditions allow them to be tightly constrained and even ruled out on purely theoretical grounds.…”
mentioning
confidence: 99%